2011
DOI: 10.1002/cd.308
|View full text |Cite
|
Sign up to set email alerts
|

The developmental roots of social responsibility in childhood and adolescence

Abstract: Social responsibility is a value orientation, rooted in democratic relationships with others and moral principles of care and justice, that motivates certain civic actions. Given its relevance for building stronger relationships and communities, the development of social responsibility within individuals should be a more concerted focus for developmental scholars and youth practitioners. During childhood and adolescence, the developmental roots of individuals' social responsibility lie in the growth of executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 44 publications
3
96
0
2
Order By: Relevance
“…And that's just what makes the world a better place … I think that has made me want to help other people and hopefully by helping them, they would wanna help other people." While previous theory and research has identified a connection between social responsibility and civic engagement [Pratt et al, 2003;Wray-Lake & Syvertsen, 2011], our interviewees with civic purpose showed that a particular orientation to social responsibility -commitment to the belief that society is interdependent -is associated with sustained and purposeful civic engagement.…”
Section: Social Responsibility Is a Common Value Among Those With CIVmentioning
confidence: 96%
See 1 more Smart Citation
“…And that's just what makes the world a better place … I think that has made me want to help other people and hopefully by helping them, they would wanna help other people." While previous theory and research has identified a connection between social responsibility and civic engagement [Pratt et al, 2003;Wray-Lake & Syvertsen, 2011], our interviewees with civic purpose showed that a particular orientation to social responsibility -commitment to the belief that society is interdependent -is associated with sustained and purposeful civic engagement.…”
Section: Social Responsibility Is a Common Value Among Those With CIVmentioning
confidence: 96%
“…This is one way that reasoning about abstract principles such as justice, equality, and liberty emerges and can lead some youth to attach to these principles as values such that they become central to their identity [Colby & Damon, 1992]. Through similar processes, young people can develop civic purpose out of a strong sense of social responsibility, which has been defined as "concern for others beyond one's own wants and needs," and described as a value that is a developmental outcome following from empathy and perspective taking [Wray-Lake & Syvertsen, 2011]. We argue, however, that social responsibility goes beyond concern for others to encompass concern for interdependent society and a personal sense of responsibility for sustaining the common good.…”
Section: Civic Purposementioning
confidence: 99%
“…The underlying motivation for civic purpose is the moral values associated with social responsibility, such as helping others, fairness, justice, equality, and rights (Wray-Lake & Syvertsen, 2011). Generally, young people develop civic purpose in response to local issues, specifically those that impact their family, friends, and neighbors, or issues that impact a community that they identify with, such as an immigrant community or the LGBT community .…”
Section: Purpose Developmentmentioning
confidence: 99%
“…A rational perception of the connotations of social responsibility and an in-depth analysis of the dual dimension of ethics and governance contained in social responsibility are conducive to more profound, systematic research in the future. [5] 社会责任品质是个体道德发展的需 要,同时也是教育的培养目标。澳大利亚的高等教育机构一直在努力制定清晰的战略,以便 在特定的学科背景下开发和评估毕业生的属性。将社会责任品质作为研究生的社会属性,并 在评估任务中明确地嵌入需要考虑社会责任在实践经验中发展的情况,将提升学生社会责任 品质这一目标的实现。 [6] 此外,人类社会发展的新变化,也使得我们开始考虑将协同(a)社会 责任(SR)、(b)创新、(c)(辩证)系统理论,作为实现必要的整体论(RH)的理论。没有社会责任 (SR),所有人的利益都很难产生。没有社会责任(SR),当前的文明也将几乎没有生存的机会。 社会责任(SR)是一个人的属性。相互依存使人诚实,使人从片面走向整体。 [7] 3.2 要素论 要素论者将社会责任品质作为系统中不可或缺的要素,通过要素的完善来促进系统的优 化。Paolo Popoli 将企业社会责任作为企业社会创新的基本要素,同时指出了企业社会责任对 企业社会的促进和保障功能。在超越企业社会责任的基础上,探讨链接企业社会责任(CSR) 和企业社会创新(CSI), 指出社会创新范式如何以及为什么通过克服 CSR 的传统"给予"逻辑来 代表商业机会,从而使社会价值创造与经济价值创造携手并进。 [8] 也有学者将企业社会责任 作为一种国际战略,指出今天的公司负责公共项目的管理和执行,因此,企业是高度"社会责 任"的,因为它们是代表公共利益行事的(尽管这不是他们做出的选择)。 [9] 迈克尔·波特和马 克·克莱默提出了一种全新的视角来看待商业和社会之间的关系,这种关系并不把企业增长和 社会福利视为一种零和游戏而将社会责任看作是一种机会,一种必不可少的要素。 [10] 社会责 任品质也是市场营销人员取得更大收益不可或缺的基本要素。 [11] 3.3 管理论 管理论者将社会责任品质作为提升管理效能,解决社会、经济等领域危机的手段。《社 会和组织信息安全责任研究手册》, [12] 揭示了当代社会管理和人力方面的信息安全问题,这 个具有里程碑意义的研究手册提供了对相关社会责任问题的评估与策略,例如雇员监控、信 息安全策略和口令身份验证等。还有学者提出媒体的"社会责任论",主张新闻自由应受社会 制约,新闻传播要对社会负责的新闻理论,从而更好地实行"有控制的新闻自由"。 [13] 社会责 任品质的提升同时也为管理社会经济危机提供一种新的非技术创新。社会经济危机可以通过 社会责任(SR)、人类必要的整体论(RH)和幸福(WB)来解决。SR 可以通过减少人的片面性来 帮助解决危机,同时 SR 和 WB 都支持 RH 行为,它们之间的创新协同作用导致了危机的解 决。 [14] …”
unclassified